2014
DOI: 10.15403/jgld.2014.1121.234.elr
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lactobacillus reuteri Supplementation in Adults with Chronic Functional Constipation: a Randomized, Double-Blind, Placebo-Controlled Trial*

Abstract: Background & Aims: There is a growing interest for the use of probiotics for chronic constipation. A recent randomized controlled trial (RCT) showed a positive effect of Lactobacillus reuteri (L. reuteri) on bowel movement frequency in infants with chronic constipation. The aim of the present study was to evaluate the effects of L. reuteri in adult patients with functional constipation.Methods: A double-blind, placebo RCT was conducted in 40 adults (18M/22F, 35±15 years) affected by functional constipation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 23 publications
5
68
2
3
Order By: Relevance
“…The prototype Lactobacillus reuteri ATCC-PTA-6475 has been originally isolated from human's mother milk. Lactobacillus reuteri is considered a typical probiotic and was shown to ameliorate infectious and non-infectious gastrointestinal disorders in both humans and animals [ 34 - 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prototype Lactobacillus reuteri ATCC-PTA-6475 has been originally isolated from human's mother milk. Lactobacillus reuteri is considered a typical probiotic and was shown to ameliorate infectious and non-infectious gastrointestinal disorders in both humans and animals [ 34 - 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence revealed that beneficial probiotics show promise for the treatment of disorder of small intestinal contractile activity caused by TBI [ 33 ]. Lactobacillus is one of the predominant probiotics in the animal’s GI tract which are defined as live microorganisms and when administered in adequate amounts, confer a health benefit to the host [ 5 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus reuteri produces a broad-spectrum antimicrobial substance during fermentation of glycerol, which revealed that glycerol fermentation was associated with the production of beta-hydroxypropionic acid and trimethylene glycol [ 6 ]. L. reuteri is used as a probiotic for chronic constipation [ 7 ], inhibits Helicobacter pylori load in humans [ 8 ], and removes cholesterol [ 2 ].…”
Section: Introductionmentioning
confidence: 99%